Survey of high-precision localization and the prospect of future evolution - Huiqiang WANG; Kaixuan GAO; Hongwu LYU (Tongxin xuebao)
Nowadays, high-precision indoor positioning service has witnessed an increasing interest because it has become the key support of many 5G major application scenarios, and the implementation technologies and mechanisms are continuously updated with advantages, disadvantages and specificities.Therefore, a timely and systematic summary of indoor-positioning was made, and that of prospects for where this domain was heading.Firstly, based on the analysis of the existing papers, summarization of this domain was proposed from two aspects, such as positioning-techniques and positioning-methods.Secondly, a classification model was put forward based on the positioning scenarios and the “hidden requirements” included were pointed out.Then, the evaluation indices system of positioning-systems was proposed and some of the existing high-accuracy positioning system was evaluated by it.Finally, the direction of evolution about high-precision indoor positioning domain was summarized, the development trend of integrated network was pointed out, and some important concepts, such as “online is inplace”, were proposed.